Synchronous and asynchronous approach to EFL teaching during COVID-19 pandemic: enactment and challenges / Nazilatul Rochmah and Salim Nabhan - Rochmah, Nazilatul; Nabhan, Salim (Universiti Teknologi MARA, Kedah, 2022)
COVID-19 outbreak brings impacts on the teaching and learning process, and the use of technology is inevitable in the situation including in EFL teaching. The study concerning the implementation and challenges of online teaching during COVID-19 pandemic is still under explored, especially in EFL teaching context. Therefore, this study aims to investigate the implementation and challenges of English teachers using synchronous and asynchronous approach for online teaching during COVID-19 outbreak. This research used qualitative case study with data collection techniques through interviews with English teachers, observations, and documents as the data source triangulation. The study was conducted at one of private schools in Indonesia. To analyze the data, the researchers used thematic analysis. The result emerges several themes regarding the implementation of synchronous and asynchronous approach to English online teaching covering the teachers' teaching instructions, media used in English online teaching, and impacts of online classroom. A dominant use of asynchronous approach done by the teachers and limited teaching and learning activities in online classroom were found in the study. In addition, concerning its challenges, the result indicated the problems of the teachers included their qualification in utilizing technology and the students' availability to access the Internet. However, teachers offered some solutions in terms of self-improvement and personal approaches to students.